Nilai Perusahaan, Keputusan Pendanaan Dan Corporate Social Responsibility Pada Perusahaan Yang Terdaftar Di Bursa Efek Indonesia 2017-2021 - Diana Karmila; Lidya Martha (AKUNTANSI 45, 2023)
Study this aim for test the influence of funding decisions and Corporate Social Responsibility on value companies listed on the Indonesia Stock Exchange . Population study is whole companies listed on the IDX for the 2017-2021 period . Sample chosen use purposive sampling method with criteria sample is companies listed on the IDX in period 2017-2021. Company that owns report financial complete in period 2017-2021, which distributes decision funding in period 2017-2021 and obtained sample 45 companies . Data source is report financial annual taken company _ through the official website of the Indonesia Stock Exchange ( www.idx.co.id ). Testing use analysis panel data regression with tool help Eviews . funding decision be measured with using DER (Debt to Equity Ratio), meanwhile Corporate Social Responsibility be measured with (CSR) as well as Company value is measured with PBV (Price to Book Value). Research results show that funding decision variable influential positive and significant on firm value, meanwhile Corporate Social Responsibility influential negative and no significant to Company Value .